Financial Quarter - Hijawi, Deema (My University, 2018)
As it is well known, Nablus is a city well known for its vast and prominent role in the Palestinian economy. Therefore, it is only natural that such a characteristic of the city should be reflected in a structure that expresses such a thing and that also plays a part in the flourishing economy of the city That is where the idea of a financial quarter in the city of Nablus originatedThe concept of the structure itself was to chose a set of sharp, yet stable lines that can firmly portray the ever-growing financial status of the city, yet also gave the feeling of safe investing to onlookers; and what expresses growth better than the arrows that signify the growing value of stocks? The building starts out as a structure a few stories high that shoots up to the sky as a sign of prosperity that will forever change the skyline of the city.